Evaluating new fault‐controlled hydrothermal dolomitization models: Insights from the Cambrian Dolomite, Western Canadian Sedimentary Basin. Issue 6 (14th May 2020) - Koeshidayatullah, Ardiansyah; Corlett, Hilary; Stacey, Jack; Swart, Peter K.; Boyce, Adrian; Robertson, Hamish; Whitaker, Fiona; Hollis, Cathy
Abstract: Fault‐controlled hydrothermal dolomitization in tectonically complex basins can occur at any depth and from different fluid compositions, including 'deep‐seated', 'crustal' or 'basinal' brines. Nevertheless, many studies have failed to identify the actual source of these fluids, resulting in a gap in our knowledge on the likely source of magnesium of hydrothermal dolomitization. With development of new concepts in hydrothermal dolomitization, the study aims in particular to test the hypothesis that dolomitizing fluids were sourced from either seawater, ultramafic carbonation or a mixture between the two by utilizing the Cambrian Mount Whyte Formation as an example. Here, the large‐scale dolostone bodies are fabric‐destructive with a range of crystal fabrics, including euhedral replacement (RD1) and anhedral replacement (RD2). Since dolomite is cross‐cut by low amplitude stylolites, dolomitization is interpreted to have occurred shortly after deposition, at a very shallow depth (<1 km). At this time, there would have been sufficient porosity in the mudstones for extensive dolomitization to occur, and the necessary high heat flows and faulting associated with Cambrian rifting to transfer hot brines into the near surface. While the δ 18 Owater and 87 Sr/ 86 Sr ratios values of RD1 are comparable with Cambrian seawater, RD2 shows higher values in both parameters. Therefore, although aspects of the fluid geochemistry are consistent with dolomitization from seawater, very high fluid temperature and salinity could be suggestive of mixing with another, hydrothermal fluid. The very hot temperature, positive Eu anomaly, enriched metal concentrations, and cogenetic relation with quartz could indicate that hot brines were at least partially sourced from ultramafic rocks, potentially as a result of interaction between the underlying Proterozoic serpentinites and CO2 ‐rich fluids. This study highlights that large‐scale hydrothermal dolostone bodies can form at shallow burial depths via mixing during fluid pulses, providing a potential explanation for the mass balance problem often associated with their genesis.